Usulan Perbaikan Fasilitas Kerja untuk Mengurangi Risiko Kerja Area Cell 2 - Kania Sahara Oktavina; Nita P.A. Hidayat; Eri Achiraenawati (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Musculoskeletal Disorders (MSDs) are still commonly found among industrial workers, particularly those performing Manual Material Handling (MMH) activities. This condition occurs among tool delivery and returns perators in Cell 2 of the Sheet Metal Forming Department at PT Dirgantara Indonesia. Operators handle 80 to 110 types of tools daily with a total load ranging from 1,014 to 3,790 kg and individual tool weights between 1 and 80 kg. These activities are performed repetitively using non-ergonomic work facilities, forcing operators to bend, squat, and lift their arms above shoulder level. Such postures lead to musculoskeletal injuries, resulting in high operator absenteeism, delays in tool distribution, and disruptions in the production of aircraft, helicopters, and aircraft components. This study applied a quantitative approach by measuring MSD complaints using the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ). Work risk assessment was conducted using the Key Indicator Method for Lifting, Holding, and Carrying of Loads (KIM-LHC) and the Risk Assessment of Pushing and Pulling (RAPP). Work facility design was developed based on anthropometric principles and simulated using CATIA V5 software. The CMDQ results showed that two operators experienced moderate to severe discomfort in the back, shoulders, neck, hands, and knees, with scores ranging from 30 to 90. KIM-LHC analysis indicated that most activities were classified at Level 3 to Level 4, while RAPP results were influenced by load weight, travel distance, and equipment conditions. Proposed improvements in the form of a magnetic crane, ergonomic handling trolley, and anthropometrically designed storage racks reduced risk level to Level 2. Abstrak. Keluhan cedera otot atau Musculoskeletal Disorders (MSDs) masih banyak ditemukan pada pekerja industri, khususnya pada aktivitas Manual Material Handling (MMH). Kondisi ini terjadi pada operator pengiriman dan pengembalian tools di Cell 2 Departemen Sheet Metal Forming PT. Dirgantara Indonesia. Operator memindahkan 80 hingga 110 jenis tools setiap hari dengan total berat 1.014 - 3.790 kg dan variasi beban 1 - 80 kg. Aktivitas dilakukan secara berulang dengan fasilitas kerja yang tidak ergonomis, sehingga operator sering membungkuk, berjongkok, dan mengangkat tangan melebihi bahu. Postur tersebut menyebabkan cedera otot yang berdampak pada tingginya ketidakhadiran operator, keterlambatan distribusi tools, dan terhambatnya proses produksi pesawat, helikopter, serta komponen pesawat. Penelitian ini menggunakan pendekatan kuantitatif dengan pengukuran keluhan MSDs menggunakan Cornell Musculoskeletal Discomfort Questionnaire (CMDQ). Penilaian risiko kerja dilakukan menggunakan Key Indicator Method for Lifting, Holding, and Carrying of Loads (KIM-LHC) dan Risk Assessment of Pushing and Pulling (RAPP). Perancangan fasilitas kerja dilakukan berdasarkan pendekatan antropometri dan disimulasikan menggunakan perangkat lunak CATIA V5. Hasil CMDQ menunjukkan dua operator mengalami keluhan pada punggung, bahu, leher, tangan, dan lutut dengan skor 30 - 90 yang termasuk kategori sedang hingga berat. Analisis KIM-LHC menunjukkan sebagian besar aktivitas berada pada Level 3 - 4, sedangkan RAPP dipengaruhi oleh beban, jarak tempuh, dan kondisi peralatan. Usulan perbaikan berupa crane magnetic, troli handling, dan rak penyimpanan sesuai antropometri menurunkan risiko kerja menjadi Level 2.